Tahfizh Camp’s Strategy in Accelerating Memorization of Al-Quran at SMPIT Al-Bina Purwakarta - Alawiyah, Widia; Qomaruddin , Muhammad; Hilmi, Fahmi Firdaus; Yani, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research describes the Tahfizh Camp Strategy in Accelerating Quran Memorization at Smpit Al Bina Purwakarta. The tahfizh camp program is one of the effective Al-Qur'an learning strategies to accelerate the memorization process. Analysis in this article by conducting research consisting of research methods, respondents aimed at school principals, tahfizh teachers and student guardians, data collection techniques and data analysis directly and including research instruments. This method integrates an intensive approach, a supportive environment, and a focused time management strategy then analyze it with Iceberg. In its implementation, the tahfizh camp is designed to create a conducive atmosphere through isolation from distractions, intensive guidance by experts, and the implementation of a strict yet flexible daily schedule to accommodate participants' needs. The program also adopts methods of repetition, memorization assistance (murajaah) and addition of memorization (ziyadah). The results of the literature review show that this tahfizh camp activity can be a way or means of accelerating memorization, strengthening the quality of memorization, and increasing the motivation and consistency of participants in memorizing the Qur'an. Thus, tahfizh camp is one of the innovative models that can be adopted by Islamic educational institutions in accelerating the memorization of the Qur'an effectively.